The impact of external plant carbon sources on nitrogen removal and microbial community structure in vertical flow constructed wetlands - Lin, Yan; Lu, Xingshun; Zhao, Manping; Ding, Xiaoyu; Lv, Hang; Wang, Lixin; Wu, Linhui (Frontiers in Environmental Science, 2023)
The present study was developed to explore nitrogen removal performance and associated microbial mechanisms of action in vertical flow constructed wetlands (VFCWs) when using external carbon sources. These analyses ultimately revealed that alkali-soaked Phragmites australis (P. australis) could serve as an effective plant carbon source, exhibiting the lower levels of total nitrogen (TN) release and the highest chemical oxygen demand (COD) of all tested carbon sources. Nitrogen removal efficiency improved following the addition of plant carbon sources, and under carbon/nitrogen (C/N) rations of 2, 4, 5, and 7, the VFCW system was able to remove 43.69%–75.76% TN, with the highest removal rate being observed at a C/N of 5. The abundance of denitrifying microorganisms such as Thiobaillus and Halomonas were also more enriched in VFCW1 than VFCW0, with stronger correlations in the microbial network community. A qPCR approach was used to analyze functional genes involved in denitrification, revealing that the addition of plant carbon sources was associated with increases in total gene abundance and the abundance of the denitrifying gene nirS, whereas no corresponding increase in amoA or nxrA abundance was observed. Higher total gene, amoA, and nxrA abundance were observed in the upper levels of these VFCW systems as compared to the lower layers, whereas nirS exhibited the opposite abundance pattern. Overall, these findings suggested that short-range denitrification is likely to be the primary denitrification process active in this VFCW system.